Adhesive sheet, method for producing adhesive sheet, and method for selecting colorant

By using acrylic polymers and metal oxides in the adhesive sheet and controlling their color parameters, the problem of insufficient integration with the black frame transparent members in the prior art is solved, and an adhesive sheet with high integration and design is achieved.

CN114761233BActive Publication Date: 2024-12-17OJI HLDG CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202080082690.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-03
Filing Date
2020-12-02
Publication Date
2024-12-17
Estimated Expiration
2040-12-02

AI Technical Summary

Technical Problem

The prior art has failed to provide an adhesive sheet with excellent integration with transparent members including black frames, especially in the absence of design and integration when the display is turned off.

Method used

By using acrylic polymer and metal oxide as colorants in the adhesive sheet, and controlling the L*, a*, b* values ​​and C1 and C2 values ​​in the L*a*b* color system, ensure the adhesive sheet The color meets a specific range, thereby achieving an adhesive sheet that is integrated with the transparent members of the black frame.

Benefits of technology

The black frame integration with the transparent member including the black frame is achieved, which improves the blackness and designability of the display in the black screen state, and enhances the overall feeling of the transparent member with the black frame.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114761233B_ABST
    Figure CN114761233B_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive sheet, a method for manufacturing an adhesive sheet, and a method for selecting a colorant. An adhesive sheet comprises an acrylic polymer and a colorant, wherein the colorant is a metal oxide, the adhesive sheet is used to bond a transparent component including a black frame, the L* value in the L*a*b* color system specified by JIS Z8781-4:2013 in the adhesive sheet is greater than 15 and less than 90, the a* value is less than 0, and the b* value is less than 0, and the adhesive sheet and the black frame of the transparent component including the black frame have excellent sense of unity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet, a method for manufacturing the adhesive sheet and a method for selecting a colorant. Background Art

[0002] Previously, display devices such as liquid crystal displays (LCDs) or input devices used in combination with display devices such as touch screens were widely used. In the manufacture of these display devices or input devices, adhesive sheets are used for bonding optical components. In recent years, in order to give design to adhesive sheets or to achieve functional concealment, adhesive sheets with a black appearance are sometimes required, and it is known that a black layer containing a black pigment is provided on a double-sided adhesive sheet in order to give light-shielding properties (see Patent Documents 1 and 2).

[0003] Patent Document 1 discloses a double-sided adhesive sheet including a laminate including a flexible base layer, first and second black layers, and first and second adhesive layers, wherein the first and second adhesive layers are outermost layers on both sides of the laminate.

[0004] Patent Document 2 discloses a black foil-like adhesive comprising an adhesive component, a black pigment, and a styrene-maleic acid resin, wherein the content of the black pigment in the black foil-like adhesive is 2% to 6% by mass.

[0005] [Prior art literature]

[0006] [Patent Document]

[0007] Patent Document 1: Japanese Patent Application Publication No. 2005-060435

[0008] Patent Document 2: Japanese Patent Application Publication No. 2013-032430 Summary of the invention

[0009] [Problems to be solved by the invention]

[0010] As described above, there is known a black adhesive sheet obtained by coloring a substrate or an adhesive, but this type of adhesive sheet is not intended to be bonded to a transparent component including a black frame or its display surface, and the design of bonding the transparent component including a black frame or its display surface to the adhesive sheet, in particular, the sense of integration with the black frame when the display is in the off state (when the power is disconnected), has not been studied.

[0011] An object of the present invention is to provide an adhesive sheet having an excellent sense of integration with a black frame including a transparent member of the black frame.

[0012] [Technical means to solve the problem]

[0013] The inventors of the present invention have conducted extensive research to solve the above-mentioned problems and have found that by mixing a metal oxide as a colorant into an adhesive sheet containing an acrylic polymer and controlling the L* value, a* value, and b* value in the L*a*b* colorimetric system of the adhesive sheet so as to satisfy a prescribed relationship, an adhesive sheet that can solve the above-mentioned problems can be obtained.

[0014] Specifically, the structure and preferred structure of the present invention are as follows.

[0015] [1] An adhesive sheet comprising an acrylic polymer and a colorant, wherein:

[0016] The colorant is a metal oxide.

[0017] The adhesive sheet is used to attach the transparent components including the black frame.

[0018] The adhesive sheet has an L* value of 15 or more and less than 90, an a* value of less than 0, and a b* value of less than 0 in the L*a*b* colorimetric system specified in Japanese Industrial Standards (JIS) Z8781-4:2013.

[0019] [2] The adhesive sheet according to [1], wherein the colorant comprises at least one metal type containing one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium.

[0020] [3] An adhesive sheet comprising an acrylic polymer and a colorant, wherein:

[0021] The colorant comprises at least one metal species containing one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium,

[0022] The adhesive sheet is used to attach the transparent components including the black frame.

[0023] The adhesive sheet has an L* value of 15 or more and less than 90, and an a* value of less than 0 in the L*a*b* colorimetric system specified in JIS Z8781-4:2013.

[0024] [4] The adhesive sheet according to any one of [1] to [3], wherein the colorant is a black metal oxide.

[0025] [5] An adhesive sheet comprising an acrylic polymer and a colorant, wherein:

[0026] The colorant is a black metal oxide.

[0027] The adhesive sheet is used to attach the transparent components including the black frame.

[0028] In the adhesive sheet, the L* value in the L*a*b* colorimetric system specified in JIS Z8781-4:2013 is 15 or more and less than 90, and the a* value is -10.0 or more and less than 0.

[0029] [6] The adhesive sheet according to any one of [1] to [5], wherein the a* value of the adhesive sheet is greater than or equal to -3.0 and less than -0.2, and the b* value is greater than or equal to -20.0 and less than 0.

[0030] [7] The adhesive sheet according to any one of [1] to [6], wherein the acrylic polymer contains acrylic acid monomer units having a crosslinkable functional group.

[0031] [8] The adhesive sheet according to any one of [1] to [7], further comprising a cross-linking agent.

[0032] [9] The adhesive sheet according to any one of [1] to [8], further comprising a UV absorber.

[0033]

[10] The adhesive sheet according to any one of [1] to [9], wherein the L* value of the adhesive sheet is 60 or more and less than 90, and the C1 value represented by the following formula 1 is 9 to 15, or

[0034] The L* value is 15 or more and less than 60, and the C2 value represented by the following formula 2 is 5.8 to 10.8.

[0035] Formula 1:

[0036] C1=0.13×L*-b*

[0037] Formula 2:

[0038] C2=0.06×L*-b*

[0039]

[11] The adhesive sheet according to

[10] , wherein the C1 value is 11 to 13, or the C2 value is 7.8 to 9.8.

[0040]

[12] A method for producing an adhesive sheet, the adhesive sheet comprising an acrylic polymer and a colorant, wherein:

[0041] The colorant is a metal oxide.

[0042] The adhesive sheet is used to adhere to the transparent component including the black frame, and the manufacturing method of the adhesive sheet includes any one of the following steps:

[0043] A step of screening an adhesive sheet, wherein the L* value in the L*a*b* colorimetric system specified in JIS Z8781-4:2013 is 15 or more and less than 90, the a* value is less than 0, and the b* value is less than 0;

[0044] A step of selecting an adhesive sheet, wherein the colorant in the adhesive sheet comprises at least one metal type containing one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium, and the L* value is greater than 15 and less than 90, and the a* value is less than 0; and

[0045] A step of screening an adhesive sheet having an L* value of 15 or more and less than 90 and an a* value of -3.0 or more and less than 0.

[0046]

[13] The method for producing an adhesive sheet according to

[12] , wherein the L* value of the adhesive sheet is 60 or more and less than 90, and the C1 value represented by the following formula 1 is 9 to 15, or

[0047] The L* value is 15 or more and less than 60, and the C2 value represented by the following formula 2 is 5.8 to 10.8.

[0048] Formula 1:

[0049] C1=0.13×L*-b*

[0050] Formula 2:

[0051] C2=0.06×L*-b*

[0052]

[14] A method for selecting a colorant for an adhesive sheet comprising an acrylic polymer and a colorant, wherein:

[0053] The colorant is a metal oxide.

[0054] The adhesive sheet is used to attach the transparent components including the black frame.

[0055] In the case of using acrylic polymer and colorant to manufacture adhesive sheet, any of the following steps may be included:

[0056] A step of selecting a colorant having an L* value of 15 or more and less than 90, an a* value of less than 0, and a b* value of less than 0 in the L*a*b* color system specified in JIS Z8781-4:2013 for the adhesive sheet;

[0057] A step of selecting a colorant including at least one metal type containing one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium, and having an L* value of 15 or more and less than 90 and an a* value of less than 0 for the adhesive sheet; and

[0058] A step of selecting a colorant having an L* value of 15 or more and less than 90 and an a* value of -3.0 or more and less than 0.

[0059]

[15] The method for selecting a colorant according to

[14] , wherein the L* value of the adhesive sheet is 60 or more and less than 90, and the C1 value represented by the following formula 1 is 9 to 15, or

[0060] The L* value is 15 or more and less than 60, and the C2 value represented by the following formula 2 is 5.8 to 10.8.

[0061] Formula 1:

[0062] C1=0.13×L*-b*

[0063] Formula 2:

[0064] C2=0.06×L*-b*

[0065]

[101] An adhesive sheet comprising an acrylic polymer and a colorant, wherein:

[0066] The colorant is a metal oxide.

[0067] The adhesive sheet is used to attach the transparent components including the black frame.

[0068] The adhesive sheet has an L* value of 60 or more and less than 90, an a* value of less than 0, and a C1 value represented by the following formula 1 of 9 to 15 in the L*a*b* colorimetric system specified in JIS Z8781-4:2013.

[0069] Formula 1:

[0070] C1=0.13×L*-b*

[0071]

[102] The adhesive sheet according to

[101] , wherein the acrylic polymer contains acrylic acid monomer units having a crosslinkable functional group.

[0072]

[103] The adhesive sheet according to

[101] or

[102] , further comprising a cross-linking agent.

[0073]

[104] The adhesive sheet according to any one of

[101] to

[103] , further comprising a UV absorber.

[0074]

[105] The adhesive sheet according to any one of

[101] to

[104] , wherein the C1 value is 11 to 13.

[0075]

[106] The adhesive sheet according to any one of

[101] to

[105] , wherein the colorant comprises at least one metal species containing one or more metal oxides selected from the group consisting of copper, iron and manganese.

[0076]

[107] A method for producing an adhesive sheet, the adhesive sheet comprising an acrylic polymer and a colorant, wherein:

[0077] The colorant is a metal oxide.

[0078] The adhesive sheet is used to attach the transparent components including the black frame.

[0079] The method for producing an adhesive sheet includes the step of selecting an adhesive sheet having an L* value of 60 or more and less than 90, an a* value of less than 0, and a C1 value of 9 to 15 in the L*a*b* colorimetric system specified in JIS Z8781-4:2013.

[0080] Formula 1:

[0081] C1=0.13×L*-b*

[0082]

[108] A method for selecting a colorant for an adhesive sheet comprising an acrylic polymer and a colorant, wherein:

[0083] The colorant is a metal oxide.

[0084] The adhesive sheet is used to attach the transparent components including the black frame.

[0085] When an adhesive sheet is manufactured using an acrylic polymer and a colorant, the step includes selecting a colorant having an L* value of 60 or more and less than 90, an a* value of less than 0, and a C1 value of 9 to 15 represented by the following formula 1 in the L*a*b* color system specified in JIS Z8781-4:2013 for the adhesive sheet.

[0086] Formula 1:

[0087] C1=0.13×L*-b*

[0088]

[201] An adhesive sheet comprising an acrylic polymer and a colorant, wherein:

[0089] The colorant is a metal oxide.

[0090] The adhesive sheet is used to attach the transparent components including the black frame.

[0091] The adhesive sheet has an L* value in the L*a*b* colorimetric system specified in JIS Z8781-4:2013 of 15 or more and less than 60, and a C2 value represented by the following formula 2 of 5.8 to 10.8.

[0092] Formula 2:

[0093] C2=0.06×L*-b*

[0094]

[202] The adhesive sheet according to

[201] , wherein the acrylic polymer contains acrylic acid monomer units having a crosslinkable functional group.

[0095]

[203] The adhesive sheet according to

[201] or

[202] , further comprising a cross-linking agent.

[0096]

[204] The adhesive sheet according to any one of

[201] to

[203] , further comprising a UV absorber.

[0097]

[205] The adhesive sheet according to any one of

[201] to

[204] , wherein the C2 value is 7.8 to 9.8.

[0098]

[206] An adhesive sheet according to any one of

[201] to

[205] , wherein the colorant comprises at least one metal species containing one or more metal oxides selected from the group consisting of copper, iron and manganese.

[0099]

[207] A method for manufacturing an adhesive sheet, the adhesive sheet comprising an acrylic polymer and a colorant, wherein:

[0100] The colorant is a metal oxide.

[0101] The adhesive sheet is used to attach the transparent components including the black frame.

[0102] The method for producing an adhesive sheet includes the step of selecting an adhesive sheet having an L* value of 15 or more and less than 60 in the L*a*b* colorimetric system specified in JIS Z8781-4:2013 and a C2 value represented by the following formula 2 of 5.8 to 10.8.

[0103] Formula 2:

[0104] C2=0.06×L*-b*

[0105]

[208] A method for selecting a colorant, wherein the colorant is used in an adhesive sheet comprising an acrylic polymer and a colorant, wherein:

[0106] The colorant is a metal oxide.

[0107] The adhesive sheet is used to attach the transparent components including the black frame.

[0108] When an adhesive sheet is manufactured using an acrylic polymer and a colorant, the step includes selecting a colorant having an L* value of 15 or more and less than 60 in the L*a*b* color system specified in JIS Z8781-4:2013 and a C2 value of 5.8 to 10.8 represented by the following formula 2.

[0109] Formula 2:

[0110] C2=0.06×L*-b*

[0111] [Effects of the Invention]

[0112] According to the present invention, it is possible to obtain an adhesive sheet having an excellent sense of integration with a black frame including a transparent member of the black frame. BRIEF DESCRIPTION OF THE DRAWINGS

[0113] Figure 1 This is a schematic diagram showing a cross section of an adhesive sheet having a release sheet.

[0114] Figure 2 This is a chart that summarizes Formula 1A, which converts Formula 1 into a relationship between L* and b* when the C1 value is a lower limit of 9, Formula 1B, which converts Formula 1 into a relationship between L* and b* when the C1 value is an upper limit of 15, and the plots obtained in each embodiment and comparative example.

[0115] Figure 3 It is a graph obtained by summarizing Formula 2A which converts Formula 2 into the relationship between L* and b* when the C2 value is the lower limit of 5.8, Formula 2B which converts Formula 2 into the relationship between L* and b* when the C2 value is the upper limit of 10.8, and the plots of b* and a* obtained in each embodiment and comparative example.

[0116] [Explanation of Symbols]

[0117] 1: Adhesive sheet with peel-off sheet

[0118] 11: Adhesive sheet

[0119] 12a: Peel-off sheet

[0120] 12b: Peel-off sheet DETAILED DESCRIPTION

[0121] Hereinafter, the present invention will be described in detail. The description of the structural elements recorded below is sometimes based on representative embodiments or specific examples, but the present invention is not limited to such embodiments. Furthermore, the numerical range represented by "to" in this specification refers to the range including the numerical values ​​recorded before and after "to" as the lower limit and the upper limit.

[0122] [Adhesive sheet]

[0123] The first embodiment of the adhesive sheet of the present invention is an adhesive sheet comprising an acrylic polymer and a colorant.

[0124] The colorant is a metal oxide.

[0125] The adhesive sheet is used to bond transparent members including a black frame, and has an L* value of 60 or more and less than 90, an a* value of less than 0, and a b* value of less than 0 in the L*a*b* colorimetric system specified in JIS Z8781-4:2013.

[0126] The second embodiment of the adhesive sheet of the present invention is an adhesive sheet comprising an acrylic polymer and a colorant.

[0127] The colorant comprises at least one metal species containing one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium,

[0128] The adhesive sheet is used to attach the transparent components including the black frame.

[0129] The adhesive sheet has an L* value of 15 or more and less than 90, and an a* value of less than 0 in the L*a*b* colorimetric system specified in JIS Z8781-4:2013.

[0130] The third embodiment of the adhesive sheet of the present invention is an adhesive sheet comprising an acrylic polymer and a colorant.

[0131] The colorant is a black metal oxide.

[0132] The adhesive sheet is used to attach the transparent components including the black frame.

[0133] In the adhesive sheet, the L* value in the L*a*b* colorimetric system specified in JIS Z8781-4:2013 is 15 or more and less than 90, and the a* value is -3.0 or more and less than 0.

[0134] The adhesive sheet of the present invention has the above structure, so the sense of unity with the black frame of the transparent member including the black frame is excellent. In the display in the state of displaying a black screen or the light-off state where the black screen is not displayed, by attaching the adhesive sheet of the present invention, the black degree of the display is improved, thereby emphasizing the sense of unity with the transparent member including the black frame around the display surface.

[0135] <Characteristics of Adhesive Sheet>

[0136] In the adhesive sheet of the present invention, the L* value in the L*a*b* colorimetric system specified in JIS Z8781-4:2013 is 15 or more and less than 90, and the a* value is less than 0.

[0137] The adhesive sheet of the present invention preferably satisfies any one of the following conditions:

[0138] (First condition) the L* value is 60 or more and less than 90, and the C1 value represented by the following formula 1 is 9 to 15; or

[0139] (Second condition) The L* value is 15 or more and less than 60, and the C2 value represented by the following formula 2 is 5.8 to 10.8.

[0140] Formula 1:

[0141] C1=0.13×L*-b*

[0142] Formula 2:

[0143] C2=0.06×L*-b*

[0144] When the first condition is satisfied, the adhesive sheet of the present invention has an L* value in the L*a*b* colorimetric system specified in JIS Z8781-4:2013 of 60 to less than 90. The L* value is preferably 65 or more, more preferably 70 or more. The L* value is preferably 85 or less, more preferably 80 or less.

[0145] On the other hand, in the adhesive sheet of the present invention that satisfies the second condition, the L* value in the L*a*b* colorimetric system specified in JIS Z8781-4:2013 is 15 or more and less than 60. The L* value is preferably 30 or more, more preferably 35 or more, and particularly preferably 40 or more. The L* value is preferably 55 or less, and more preferably 50 or less.

[0146] By setting the L* value of the adhesive sheet to the range, the black color rendering degree of the display etc. can be more effectively improved. When the adhesive sheet is attached to a display etc. showing a black screen, it is preferred to improve its design. Specifically, when the adhesive sheet is attached to a display showing a black screen, the black color rendering degree of the display (the preferred degree of black) can be improved. As a result, the sense of unity with the transparent member including the black frame can be improved. It is further preferred to improve the design of the transparent member including the black frame. The L* value of the adhesive sheet is preferably controlled by controlling the type or amount of the colorant or controlling the thickness of the adhesive sheet.

[0147] The a* value in the L*a*b* colorimetric system specified by JIS Z8781-4:2013 in the adhesive sheet of the present invention is preferably less than 0, more preferably less than -0.2, and particularly preferably less than -0.4. The a* value is preferably greater than -10.0, more preferably greater than -3.0, particularly preferably greater than -2.0, and further particularly preferably greater than -1.0. By setting the a* value of the adhesive sheet within the range, the sense of unity with the transparent member including the black frame can be improved.

[0148] The b* value in the L*a*b* colorimetric system specified by JIS Z8781-4:2013 in the adhesive sheet of the present invention is preferably above -20.0, more preferably above -10.0. The b* value when the second condition is met is particularly preferably above -6.5, and the b* value when the first condition is met is particularly preferably above -5.0. The b* value is preferably less than 0, more preferably below -0.4. By setting the b* value of the adhesive sheet to within the range, the sense of unity with the transparent component including the black frame can be improved. The a* value and b* value of the adhesive sheet are preferably controlled by controlling the type or amount of the colorant, or controlling the type or amount of the ultraviolet absorber.

[0149] The adhesive sheet of the present invention preferably has a C1 value of 9 to 15 as represented by the following formula 1, and the C1 value is more preferably 10 or more, and particularly preferably 11 or more. The C1 value is preferably 14 or less, and more preferably 13 or less. By setting the C1 value of the adhesive sheet within the range, the sense of unity with the transparent member including the black frame can be improved. The C1 value of the adhesive sheet is preferably controlled by controlling the type of colorant or the type of ultraviolet absorber.

[0150] Formula 1:

[0151] C1=0.13×L*-b*

[0152] The adhesive sheet of the present invention preferably has a C2 value of 5.8 to 10.8, more preferably 6.8 or more, and particularly preferably 7.8 or more, as represented by the following formula 2. The C2 value is preferably 10.3 or less, more preferably 9.8 or less. By setting the C2 value of the adhesive sheet to be within the range, the sense of unity with the transparent member including the black frame can be improved. The C2 value of the adhesive sheet is preferably controlled by controlling the type of colorant or the type of ultraviolet absorber.

[0153] Formula 2:

[0154] C2=0.06×L*-b*

[0155] The thickness of the adhesive sheet is preferably 1 μm or more, more preferably 10 μm or more, and more preferably 20 μm or more. In addition, the thickness of the adhesive sheet is preferably 5000 μm or less, more preferably 3000 μm or less, and more preferably 1000 μm or less. By setting the thickness of the adhesive sheet to below the upper limit, water vapor can be prevented from infiltrating from the end to improve durability. On the other hand, by setting the thickness of the adhesive sheet to above the lower limit, the handling of the adhesive sheet can be facilitated, and it is easy to use as an optical component bonding application requiring thin filmization.

[0156] <Structure of adhesive sheet>

[0157] The adhesive sheet of the present invention may be a single-layer adhesive sheet. In addition, the adhesive sheet may be a single-sided adhesive sheet including a substrate (preferably a transparent substrate) on a single side, or may be a double-sided adhesive sheet. As a double-sided adhesive sheet, there may be listed: a single-layer adhesive sheet comprising an adhesive layer, a multi-layer adhesive sheet in which a plurality of adhesive layers are stacked, a multi-layer adhesive sheet having other adhesive layers stacked between the adhesive layer and the adhesive layer, a multi-layer adhesive sheet having a support stacked between the adhesive layer and the adhesive layer, an adhesive layer stacked on a single side of the support and a multi-layer adhesive sheet having another adhesive layer stacked on the other side. In the case where the double-sided adhesive sheet has a support, it is preferred to use a transparent support as the support. As a support, a general film used in the optical field in the same manner as a transparent substrate may be used. This double-sided adhesive sheet is also excellent in transparency as an adhesive sheet as a whole, and therefore can be suitable for optical components to be attached to each other.

[0158] like Figure 1 As shown, the present invention may also relate to an adhesive sheet with a release sheet, which includes a release sheet 12a and a release sheet 12b on both surfaces of an adhesive sheet 11. Examples of the release sheet include a release laminate having a release sheet substrate and a release layer provided on one side of the release sheet substrate, or a polyolefin film such as a polyethylene film or a polypropylene film as a low-polarity substrate.

[0159] The release sheet substrate in the release laminate can be paper or polymer film. In optical applications, polymer film can be preferably used to prevent the mixing of foreign matter. As the release agent constituting the release layer, for example, a general-purpose addition type or condensation type silicone release agent or a compound containing a long-chain alkyl group can be used. It is particularly preferred to use a highly reactive addition type silicone release agent.

[0160] Specific examples of silicone-based release agents include BY24-4527 and SD-7220 manufactured by Toray Dow Corning Silicone Co., Ltd. or KS-3600, KS-774, and X62-2600 manufactured by Shin-Etsu Chemical Co., Ltd. In addition, it is preferred that the silicone-based release agent contain a silicone-based release agent having a SiO2 unit and a (CH3)3SiO 1 / 2 Unit or CH2=CH(CH3)SiO 1 / 2 The organosilicon compound having a unit is a silicone resin. Specific examples of the silicone resin include BY24-843, SD-7292, SHR-1404 manufactured by Toray Dow Corning Silicone Co., Ltd. and KS-3800, X92-183 manufactured by Shin-Etsu Chemical Co., Ltd.

[0161] As the releasable laminate sheet, commercially available products may be used, for example, a heavy release film made of a release-treated polyethylene terephthalate film manufactured by Mitsubishi Chemical Corporation or a light release film made of a release-treated polyethylene terephthalate film manufactured by Mitsubishi Chemical Corporation.

[0162] In the case where the adhesive sheet of the present invention is a double-sided adhesive sheet, it is preferably a pair of release sheets having different release forces. That is, in order to facilitate peeling, the release sheets are preferably provided so that the release properties of one release sheet and the other release sheet are different. If the release properties from one release sheet are different from the release properties from the other release sheet, it is easy to peel only the release sheet with higher release properties first.

[0163] <Composition of adhesive sheet>

[0164] (Acrylic polymer)

[0165] The acrylic polymer is not particularly limited as long as it has acrylic acid monomer units, and is preferably an acrylic acid copolymer. As an acrylic acid copolymer, for example, it is preferably a copolymer containing a non-crosslinkable (meth)acrylate unit (a1) and an acrylic acid monomer unit (a2) having a crosslinkable functional group. Furthermore, in this specification and claims, "unit" is a repeating unit (monomer unit) constituting a polymer. In addition, an acrylic acid polymer refers to a (meth)acrylic acid polymer, that is, it also includes a methacrylic acid polymer.

[0166] The non-crosslinking (meth)acrylate unit (a1) is preferably a repeating unit derived from an alkyl (meth)acrylate. Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, stearyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and the like. These may be used alone or in combination of two or more.

[0167] Among the alkyl (meth)acrylates, at least one selected from methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate is preferred in terms of improving adhesiveness.

[0168] The acrylic monomer unit (a2) having a crosslinkable functional group is preferably at least one selected from the group consisting of a carboxyl group-containing monomer unit, a hydroxyl group-containing monomer unit, an amino group-containing monomer unit, and a glycidyl group-containing monomer unit, and more preferably at least one selected from the group consisting of a hydroxyl group-containing monomer unit, an amino group-containing monomer unit, and a glycidyl group-containing monomer unit. That is, the acrylic polymer preferably has at least one crosslinkable functional group selected from the group consisting of a carboxyl group, a hydroxyl group, an amino group, an amide group, a glycidyl group, and an isocyanate group, and more preferably has at least one crosslinkable functional group selected from the group consisting of a hydroxyl group, an amino group, an amide group, a glycidyl group, and an isocyanate group.

[0169] Examples of the carboxyl group-containing monomer unit include acrylic acid and methacrylic acid.

[0170] The hydroxyl-containing monomer unit is a repeating unit derived from a hydroxyl-containing monomer. Examples of the hydroxyl-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxypropyl (meth)acrylate, (meth)acrylates [(mono-, di-, or poly-)alkylene glycol] esters such as (meth)acrylate mono(diethylene glycol) ester, and (meth)acrylate lactones such as (meth)acrylate monocaprolactone.

[0171] Examples of the amino group-containing monomer unit include repeating units derived from amino group-containing monomers such as (meth)acrylamide and allylamine.

[0172] Examples of the glycidyl group-containing monomer unit include repeating units derived from a glycidyl group-containing monomer such as glycidyl (meth)acrylate.

[0173] The content of the acrylic acid monomer units (a2) having a crosslinkable functional group in the acrylic polymer is preferably 0.01% to 40% by mass, and more preferably 0.5% to 35% by mass. By setting the content of the acrylic acid monomer units (a2) having a crosslinkable functional group within the above range, it is easy to control the crosslinking property and adhesiveness of the acrylic polymer.

[0174] The acrylic polymer may further contain a unit derived from an alkoxyalkyl-containing (meth)acrylate. The alkoxyalkyl-containing (meth)acrylate is an alkoxyalkyl (meth)acrylate. As the alkoxyalkyl (meth)acrylate, for example, preferably an alkoxyalkyl (meth)acrylate in which the number of carbon atoms of the alkoxy group is 1 to 12 and the number of carbon atoms of the alkylene group bonded to the alkoxy group is 1 to 18. The number of carbon atoms of the alkoxy group is preferably 1 to 8, more preferably 1 to 4, and particularly preferably 1 or 2. In addition, the number of carbon atoms of the alkylene group bonded to the alkoxy group is preferably 1 to 12, further preferably 1 to 8, further preferably 1 to 4, and particularly preferably 1 to 3.

[0175] Examples of such alkoxyalkyl (meth)acrylates include 2-methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxymethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate.

[0176] The acrylic polymer may further include units derived from nitrogen-containing monomers. Nitrogen-containing monomers are monomers containing nitrogen elements in one molecule. Examples of nitrogen-containing monomers include dimethylacrylamide, diethylacrylamide, acrylamide, hydroxyethylacrylamide, hydroxymethylacrylamide, methoxymethylacrylamide, ethoxymethylacrylamide, dimethylaminoethylacrylamide, N-vinylcaprolactam, N-vinyl-2-pyrrolidone, (methyl)dimethylaminoethyl acrylate, N-vinylformamide, etc. Among them, the nitrogen-containing monomer is preferably at least one selected from acrylamide derivatives, amino-containing monomers, and nitrogen-containing heterocyclic monomers, and more preferably acrylamide derivatives. Acrylamide derivatives are further preferably at least one selected from dimethylacrylamide, diethylacrylamide, and acrylamide, and diethylacrylamide is particularly preferred.

[0177] The acrylic polymer may have other monomer units as required. The other monomers may be monomers that can be copolymerized with the acrylic monomers, and examples thereof include (meth)acrylonitrile, vinyl acetate, styrene, vinyl chloride, vinyl pyrrolidone, vinyl pyridine, etc. The content of the other monomer units in the acrylic polymer is preferably 20% by mass or less, and more preferably 15% by mass or less.

[0178] The acid value of the acrylic polymer is preferably less than 50 mgKOH / g, more preferably less than 40 mgKOH / g, and further preferably less than 30 mgKOH / g, further preferably less than 20 mgKOH / g, further more preferably less than 10 mgKOH / g, and particularly preferably less than 5 mgKOH / g. Furthermore, the acid value of the acrylic polymer may also be 0 mgKOH / g. By setting the acid value of the acrylic polymer within the range, the decolorization of the adhesive sheet can be effectively suppressed. Specifically, by setting the acid value of the acrylic polymer within the range, even if the adhesive sheet is placed for a long time under high temperature and high humidity conditions, the rise of the total light transmittance can be suppressed. The total light transmittance of the adhesive sheet before and after being placed at 85°C and 85% relative humidity for 240 hours is measured, and the change in the total light transmittance calculated from the value is preferably less than 10%. Furthermore, the total light transmittance after the adhesive sheet is placed at 85°C and 85% relative humidity for 240 hours is preferably less than 85%. Furthermore, the change in the total light transmittance can be calculated by the following formula.

[0179] Change (%) = (total light transmittance of the sample before treatment) - (total light transmittance of the sample after treatment)

[0180] The acid value of acrylic polymer is measured in accordance with JIS K 0070 (1992). Specifically, firstly, accurately weigh about 2 g of the sample in a 100 ml conical flask using a precision balance, and add 10 ml of a mixed solvent of ethanol / diethyl ether = 1 / 1 (weight ratio) to dissolve it. Furthermore, add 1 to 3 drops of phenolphthalein ethanol solution to the container as an indicator, and stir thoroughly until the sample is uniform. Titrate it with 0.1N potassium hydroxide-ethanol solution, and the neutralization endpoint is when the light red color of the indicator lasts for 30 seconds. The value obtained based on the result and using the following calculation formula (1) is set as the acid value of the sample.

[0181] Acid value (mgKOH / g) = [B × f × 5.611] / S (1)

[0182] In the calculation formula (1), B is the amount of 0.1N potassium hydroxide-ethanol solution used (ml), f is the factor of 0.1N potassium hydroxide-ethanol solution, and S is the amount of sample collected (g).

[0183] The weight average molecular weight of the acrylic polymer is preferably 100,000 to 2,000,000, and more preferably 200,000 to 1,500,000. Furthermore, the weight average molecular weight of the acrylic polymer is a value before cross-linking using a cross-linking agent described later. The weight average molecular weight is a value determined by size exclusion chromatography (SEC) based on a polystyrene standard. As the acrylic polymer, a commercially available acrylic polymer can be used, and an acrylic polymer synthesized by a known method can also be used.

[0184] The solution viscosity of the acrylic polymer is preferably 1,000 to 10,000 mPa·s, and more preferably 1,500 to 8,000 mPa·s, as measured by the solution viscosity of a 35% by mass solution at 23°C.

[0185] (Colorant)

[0186] The adhesive sheet of the present invention contains a colorant. The colorant is a metal oxide.

[0187] By using metal oxide as a colorant, the sense of unity with the black frame, the design, and the visibility of the adhesive sheet can be more effectively improved. In addition, compared with the case of using a dye, the use of metal oxide is less likely to hinder the cross-linking reaction during the manufacture of the adhesive sheet, and the color resistance is also excellent.

[0188] As a metal oxide, a black pigment is preferred. As metal oxides, examples include: copper oxide, ferrosoferric oxide, manganese dioxide, barium titanate, potassium titanate, iron titanate, copper-chromium oxide, copper-manganese oxide, copper-iron-manganese oxide, copper-chromium-manganese oxide or copper-iron-chromium oxide, titanium oxide nitride or titanium oxide and other titanium blacks. Furthermore, in this specification, metal oxide nitride is included in the metal oxide. Among them, the colorant is more preferably a metal oxide containing at least one metal species selected from the group consisting of copper, iron, manganese and titanium, and is particularly preferably a metal oxide containing at least one metal species selected from the group consisting of copper, iron and manganese. The so-called metal species refers to the metal ions that constitute the metal oxide. By selecting the species as the colorant, the coloring stability is good. The metal species may be single or multiple (single oxide or composite oxide).

[0189] As the colorant, one metal oxide may be used alone or as a mixture of two or more metal oxides.

[0190] The colorant is preferably a microparticle. The primary average particle size of the colorant is preferably 0.01 μm or more. In addition, the primary average particle size of the colorant is preferably less than 5 μm, more preferably less than 3 μm, further preferably less than 1 μm, and particularly preferably less than 0.5 μm. By setting the primary average particle size of the colorant to within the above range, the visibility of the adhesive sheet can be more effectively improved.

[0191] The content of the colorant per unit area in the adhesive sheet when the first condition is satisfied is preferably 0.03 g / m 2 ~0.25g / m 2 , more preferably 0.05 g / m 2 ~0.20g / m 2 , particularly preferably 0.10 g / m 2 ~0.18g / m 2 .

[0192] The content of the colorant per unit area in the adhesive sheet when the second condition is satisfied is preferably 0.25 g / m 2 ~1.10g / m 2 , more preferably 0.27 g / m 2 ~0.80g / m 2 , particularly preferably 0.30 g / m 2 ~0.50g / m 2 .

[0193] Regardless of the thickness of the adhesive layer of the adhesive sheet, as long as the colorant is contained within the above range per unit area, visibility and a sense of unity with the black frame of the transparent member including the black frame can be improved.

[0194] The colorant is preferably mixed with the acrylic polymer in a state of being dispersed in a dispersion resin. Examples of the dispersion resin include polyester resins, urethane resins, acrylic resins, and polyether resins.

[0195] (Crosslinking agent)

[0196] The adhesive sheet of the present invention preferably contains a crosslinking agent. The crosslinking agent can be suitably selected considering the reactivity of the crosslinking functional group possessed by the acrylic polymer. For example, it can be selected from the known crosslinking agents such as isocyanate compounds, epoxy compounds, oxazoline compounds, aziridine compounds, metal chelate compounds, butylated melamine compounds, etc. Among these, it is preferred to use isocyanate compounds or epoxy compounds in terms of being able to easily make hydroxyl-containing (meth) acrylates crosslinked. That is, the crosslinking agent is preferably selected from at least one of difunctional or higher epoxy compounds and difunctional or higher isocyanate compounds, more preferably difunctional or higher isocyanate compounds.

[0197] As isocyanate compounds, for example, toluene diisocyanate, xylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, etc. As commercially available examples, toluene diisocyanate compounds (manufactured by Tosoh Co., Ltd., Coronate L), toluene diisocyanate adducts of trimethylolpropane (manufactured by Tosoh Co., Ltd., Coronate L-55E), and xylene diisocyanate compounds (manufactured by Mitsui Chemicals Co., Ltd., Takenate D-110N) can be cited.

[0198] Examples of the epoxy compound include ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycerol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, tetraglycidyl xylene diamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, trimethylolpropane polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, and sorbitol polyglycidyl ether.

[0199] Examples of commercially available products include 1,3-bis(N,N-diglycidylaminomethyl)benzene (or N,N,N′,N′-tetraglycidyl-1,3-phenylenedi(methylamine); manufactured by Mitsubishi Gas Chemical Co., Ltd., TETRAD-X), 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., TETRAD-C), and the like.

[0200] The content of the crosslinking agent in the adhesive sheet can be appropriately selected according to the desired adhesion, but is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the acrylic polymer. By setting the content of the crosslinking agent within the range, the processability of the adhesive sheet can be further improved. Furthermore, as a crosslinking agent, one can be used alone or two or more can be used in combination. In the case of using two or more, it is preferred that the total mass is within the range.

[0201] (Ultraviolet light absorber)

[0202] The adhesive sheet of the present invention may contain an ultraviolet absorber. The ultraviolet absorber can be appropriately selected considering the sense of unity with the black frame, the design and the light resistance (resistance to discoloration) of these. For example, it can be selected from the known ultraviolet absorbers such as benzotriazole compounds, triazine compounds, benzophenone compounds, benzoate compounds, hindered amine compounds (light stabilizers). Among these, from the perspective of strongly absorbing the long wavelength part (UV-A region) of ultraviolet rays, it is preferred to use hydroxyphenyl triazine compounds.

[0203] Examples of the triazine compound include hydroxyphenyltriazine, etc. Examples of commercially available products include hydroxyphenyltriazine compounds (produced by BASF Japan Co., Ltd., Tinuvin 477), etc.

[0204] Examples of benzotriazole compounds include benzotriazole, etc. Examples of commercially available products include phenylpropionic acid, 3-(2H-benzotriazole-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-, C7-9-branched and straight-chain alkyl esters (produced by BASF Japan Co., Ltd., Tinuvin 384-2), etc.

[0205] The content of the ultraviolet light absorber in the adhesive sheet can be appropriately selected according to the desired light resistance (resistance to discoloration), but relative to 100 parts by mass of acrylic polymer, preferably 0.01 parts by mass to 5 parts by mass, more preferably 0.1 parts by mass to 3 parts by mass. By setting the content of the ultraviolet light absorber to within the range, the processability of the adhesive sheet can be further improved. Furthermore, as an ultraviolet light absorber, one can be used alone or two or more can be used in combination. In the case of using two or more, it is preferably that the total mass is within the range.

[0206] (Solvent)

[0207] The adhesive composition used to form the adhesive sheet of the present invention may contain a solvent. In such a case, the solvent is used to improve the coating suitability of the adhesive composition. Examples of the solvent include hydrocarbons such as hexane, heptane, octane, toluene, xylene, ethylbenzene, cyclohexane, and methylcyclohexane; halogenated hydrocarbons such as dichloromethane, trichloroethane, trichloroethylene, tetrachloroethylene, and dichloropropane; alcohols such as methanol, ethanol, propanol, isopropyl alcohol, butanol, isobutyl alcohol, and diacetone alcohol; ethers such as diethyl ether, diisopropyl ether, dioxane, and tetrahydrofuran; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, isophorone, and cyclohexanone; esters such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, amyl acetate, and ethyl butyrate; polyols such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monomethyl ether acetate, and their derivatives.

[0208] The content of the solvent in the adhesive composition is not particularly limited, but is preferably 25 to 500 parts by mass, more preferably 30 to 400 parts by mass, based on 100 parts by mass of the acrylic polymer.

[0209] The content of the solvent is preferably 10% to 90% by mass, more preferably 20% to 80% by mass, relative to the total mass of the adhesive composition. The solvent may be used alone or in combination of two or more. When two or more solvents are used in combination, the total mass is preferably within the above range.

[0210] (Other ingredients)

[0211] In the range that does not impair the effect of the present invention, the adhesive sheet may contain other components other than those described above. As other components, components known as adhesive additives can be cited. For example, it can be selected from plasticizers, antioxidants, metal corrosion inhibitors, adhesion imparting agents, silane coupling agents, acid capture agents, etc. as needed.

[0212] Examples of the plasticizer include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristic acid, vinyl palmitic acid, vinyl stearate, vinyl cyclohexanecarboxylate, vinyl carboxylate such as vinyl benzoate, and vinyl esters of carboxylic acids; and styrene.

[0213] Examples of the antioxidant include phenolic antioxidants, amine antioxidants, lactone antioxidants, phosphorus antioxidants, sulfur antioxidants, etc. These antioxidants may be used alone or in combination of two or more.

[0214] As the metal corrosion inhibitor, benzotriazole-based resins are preferred examples in terms of compatibility with the adhesive and high degree of effect.

[0215] Examples of the tackifier include rosin-based resins, terpene-based resins, terpene-phenol-based resins, coumarone-indene-based resins, styrene-based resins, xylene-based resins, phenol-based resins, and petroleum resins.

[0216] Examples of the silane coupling agent include mercaptoalkoxysilane compounds (eg, mercapto-substituted alkoxy oligomers).

[0217] <Application of adhesive sheet>

[0218] The adhesive sheet of the present invention is used for bonding a transparent member including a black frame. If a black portion exists in a part of the transparent member, the black portion is set as the black frame. That is, the black frame is not limited to surrounding the entire circumference of the transparent member.

[0219] As a transparent member including a black frame, components such as windows of buildings, side glass of vehicles, or optical components such as touch screens or image display devices can be listed. Among them, the adhesive sheet of the present invention is preferably used for bonding optical components. As an optical member including a black frame, a smart phone, a television, and a vehicle-mounted display can be listed, and a vehicle-mounted display is particularly preferred. As a vehicle-mounted display, it can be listed: a car navigation system; a head-up display (head-up display, HUD); a rear monitor, a side mirror (side mirror) display, a rear-view mirror (rear-view mirror), and other interior mirror displays; a center information display (center information display, CID), an instrument panel, a multi-function information display, a digital meter, and other functional displays; an on-dash monitor, a headrest monitor (head rest monitor), a sun visor monitor, and other set-up displays; rear seat entertainment (rear seat entertainment, RSE), and other entertainment displays.

[0220] When the adhesive sheet of the present invention is used for bonding optical components, the adhesive sheet is preferably used for bonding to various structural components in optical products or an anti-scattering film bonded to the outermost cover glass (cover lens), and is particularly preferably used for bonding to a touch screen. As a touch screen including a black frame, in particular, a touch screen display of a car navigation system or a CID can be cited.

[0221] As structural members of the touch screen, for example, there can be listed: an ITO film (film) in which an ITO film is provided on a transparent resin film, an ITO glass in which an ITO film is provided on the surface of a glass plate, a transparent conductive film in which a conductive polymer is coated on a transparent resin film, a hard coating film, an anti-fingerprint film, etc. As structural members of the image display device, for example, there can be listed: an anti-reflection film, an orientation film, a polarizing film, a phase difference film, a brightness enhancement film, etc. used in a liquid crystal display device.

[0222] Examples of materials used for these members include glass, polycarbonate, polyethylene terephthalate, polymethyl methacrylate, polyethylene naphthalate, cycloolefin polymer, triacetyl cellulose, polyimide, and cellulose acylate.

[0223] [Method for producing adhesive sheet]

[0224] There is no particular limitation on the method for producing the adhesive sheet of the present invention.

[0225] <Step of applying the adhesive composition to form a coating film>

[0226] The method for producing an adhesive sheet preferably includes a step of applying the adhesive composition on a release sheet to form a coating film.

[0227] The adhesive composition can be applied using a known coating device, such as a blade coater, an air knife coater, a roll coater, a rod coater, a gravure coater, a micro gravure coater, a rod blade coater, a lip coater, a die coater, a curtain coater, etc.

[0228] <Step of Heating the Coating Film>

[0229] The method for manufacturing the adhesive sheet preferably includes a step of heating the coating. In the case described above, when heating the coating formed by applying the adhesive composition, a known heating device such as a heating furnace or an infrared lamp can be used. After heating the coating, an aging treatment can be performed by allowing the adhesive sheet to stand for a certain period of time at a certain temperature. The aging treatment can be performed, for example, by standing at 23°C for 7 days.

[0230] The present invention may also relate to a laminate having the adhesive sheet and a transparent member, and a method for producing the laminate having the adhesive sheet and a transparent member. When producing the laminate, the method includes a step of bonding the adhesive sheet to the transparent member.

[0231] <Steps for Screening Adhesive Sheets>

[0232] The method for manufacturing the adhesive sheet of the present invention preferably includes a step of screening the adhesive sheet. Specifically, the method for manufacturing the adhesive sheet of the present invention is preferably a method for manufacturing an adhesive sheet comprising an acrylic polymer and a colorant, the colorant is a metal oxide, the adhesive sheet is used to adhere to a transparent component including a black frame, and includes any of the following steps:

[0233] A step of screening an adhesive sheet, wherein the L* value in the L*a*b* colorimetric system specified in JIS Z8781-4:2013 is 15 or more and less than 90, the a* value is less than 0, and the b* value is less than 0;

[0234] A step of selecting an adhesive sheet, wherein the colorant in the adhesive sheet comprises at least one metal type containing one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium, and the L* value is greater than 15 and less than 90, and the a* value is less than 0; and

[0235] A step of screening an adhesive sheet having an L* value of 15 or more and less than 90 and an a* value of -3.0 or more and less than 0.

[0236] In the step of screening the adhesive sheet, the screened adhesive sheet is more preferably:

[0237] The L* value is 60 or more and less than 90, and the C1 value represented by the following formula 1 is 9 to 15; or

[0238] The L* value is 15 or more and less than 60, and the C2 value represented by the following formula 2 is 5.8 to 10.8.

[0239] Formula 1:

[0240] C1=0.13×L*-b*

[0241] Formula 2:

[0242] C2=0.06×L*-b*

[0243] There is no particular limitation on the steps for screening the adhesive sheet. For example, the L* value, a* value, and b* value of the sample of the state of the adhesive sheet manufactured by the method or the state of the laminated body of the adhesive sheet and the transparent member can be measured, and the C1 value or C2 value can be calculated, and only the samples within the range of each value can be screened as the adhesive sheet of the present invention, and the remaining defective products that are out of the range of each value can be removed.

[0244] Alternatively, commercially available adhesive sheets may be used as samples, and their L* values, a* values, and b* values ​​may be measured to calculate the C1 value or the C2 value. Only samples within the range of each value may be selected as the adhesive sheets of the present invention, and the remaining defective products that are outside the range of each value may be removed.

[0245] In addition, the state of the adhesive sheet or the state of the laminated body having the adhesive sheet and the transparent member can be made into a commercially available adhesive composition by the method, and the obtained product is set as a sample, and the L* value, a* value and b* value of the sample are measured, and the C1 value or C2 value is calculated, and only the samples within the range of each value are screened as the adhesive sheet of the present invention, and the remaining defective products that are out of the range of each value are removed. In the case described above, when a plurality of defective products that are out of the range of each value are manufactured, it is preferred to further perform the step of adding the preferred colorant, etc. to the commercially available adhesive composition to adjust the composition of the adhesive composition to manufacture the adhesive sheet.

[0246] [How to select colorant]

[0247] The method for selecting a colorant of the present invention is a method for selecting a colorant for an adhesive sheet comprising an acrylic polymer and a colorant, wherein the colorant is a metal oxide, and the adhesive sheet is used for bonding a transparent member including a black frame.

[0248] In the case of using acrylic polymer and colorant to manufacture adhesive sheet, any of the following steps may be included:

[0249] A step of selecting a colorant having an L* value of 60 or more and less than 90, an a* value of less than 0, and a b* value of less than 0 in the L*a*b* color system specified in JIS Z8781-4:2013 for the adhesive sheet;

[0250] A step of selecting a colorant including at least one metal type containing one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium, and having an L* value of 15 or more and less than 90 and an a* value of less than 0 for the adhesive sheet; and

[0251] A step of selecting a colorant having an L* value of 15 or more and less than 90 and an a* value of -3.0 or more and less than 0.

[0252] In the step of selecting a colorant, the adhesive sheet is more preferably:

[0253] The L* value is 60 or more and less than 90, and the C1 value represented by the following formula 1 is 9 to 15; or

[0254] The L* value is 15 or more and less than 60, and the C2 value represented by the following formula 2 is 5.8 to 10.8.

[0255] Formula 1:

[0256] C1=0.13×L*-b*

[0257] Formula 2:

[0258] C2=0.06×L*-b*

[0259] As the step of selecting colorant, there is no particular restriction. For example, the preferred acrylic polymer can be added to any colorant to prepare an adhesive composition, an adhesive sheet can be manufactured, the state of the adhesive sheet manufactured using the method or the state of the laminated body with the adhesive sheet and the transparent member can be measured, the L* value, a* value and b* value of the sample can be calculated, the C1 value or C2 value can be calculated, and the sample within the range of each value can be confirmed. In particular, the b* value, C1 value and C2 value vary greatly according to the type of colorant, so the colorant of the adhesive sheet of the present invention can be selected to be easy to manufacture by this step of selecting the colorant.

[0260] [Example]

[0261] The following examples and comparative examples are listed to more specifically illustrate the features of the present invention. The materials, usage amounts, ratios, processing contents, processing sequences, etc. shown in the following examples may be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention should not be construed in a limited manner by the specific examples shown below.

[0262] [Example 1]

[0263] <Synthesis of Acrylic Polymer A>

[0264] Acrylic polymer A was prepared by solution polymerization in ethyl acetate. Butyl acrylate (BA) and 2-hydroxyethyl acrylate (2HEA) were prepared in a mass ratio of 70:30, and azobisisobutyronitrile (AIBN) as a free radical polymerization initiator was dissolved in the solution. The solution was heated to 60°C for random copolymerization to obtain acrylic polymer A. The solution viscosity of a 35% by mass solution of the acrylic polymer A at 23°C was 6,400 mPa·s. In addition, the acid value of acrylic polymer A was 0.0 mgKOH / g.

[0265] <Preparation of Adhesive Composition>

[0266] An acrylic polymer A, an isocyanate crosslinking agent (an ethyl acetate solution of toluene diisocyanate adduct of trimethylolpropane, manufactured by Tosoh Co., Ltd., Coronate L-55E), an MO colorant (copper, iron, manganese-based oxides, i.e., metal oxides, manufactured by Dainichi Seika Industries, Ltd., TM Black 3550), an ultraviolet absorber C (a hydroxyphenyltriazine-based compound, manufactured by BASF Japan, Tinuvin 477), an ultraviolet absorber D (a benzotriazole-based compound, manufactured by BASF Japan, Tinuvin 384-2) and a solvent (ethyl acetate) were mixed to obtain an adhesive composition having a solid content concentration of 30% and containing 0.5 parts by mass of the crosslinking agent, 0.06 parts by mass of the colorant, and 2.00 parts by mass of the ultraviolet absorber in total, based on 100 parts by mass of the acrylic polymer A.

[0267] <Preparation of Adhesive Sheet>

[0268] The adhesive composition was applied to a first release sheet (a heavy release film, a polyethylene terephthalate film produced by Mitsubishi Chemical Co., Ltd., and subjected to a release treatment). The coating was performed using a YD-type scraper produced by Yoshimitsu Seiki Co., Ltd., in such a manner that the thickness after drying was 100 μm. Thereafter, the adhesive sheet having an adhesive layer was formed by drying at 100° C. for 3 minutes using a hot air dryer to remove the solvent.

[0269] A second release sheet (light release film, manufactured by Mitsubishi Chemical Co., Ltd.) having a higher one-sided release property than the first release sheet was subjected to a release treatment to obtain an adhesive sheet with a release sheet, i.e., an adhesive sheet of Example 1. In the adhesive sheet of Example 1, the content per unit area of ​​the MO colorant contained in the adhesive layer was 0.06 g / m 2 In the adhesive sheets of other examples and comparative examples, the content per unit area of ​​the MO colorant contained in the adhesive layer is proportional to the blending amount of the MO colorant in the adhesive composition and the thickness of the adhesive sheet after drying.

[0270] [Example 2]

[0271] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 1 except that the amount of the colorant blended was changed so that the content of the MO colorant was 0.17 parts by mass and the thickness of the adhesive sheet after drying was 50 μm.

[0272] [Example 3]

[0273] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 1 except that the amount of the colorant blended was changed so that the content of the MO colorant became 0.17 parts by mass.

[0274] [Example 4]

[0275] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 1 except that the thickness of the adhesive sheet after drying was changed to 250 μm.

[0276] [Example 5]

[0277] An acrylic polymer A, an epoxy crosslinking agent (N,N,N′,N′-tetraglycidyl-1,3-phenylenedi(methylamine), manufactured by Mitsubishi Gas Chemical Co., Ltd., TETRAD-X), an MO colorant (copper, iron, manganese-based oxides, i.e., metal oxides, manufactured by Dainichi Seika Industries, Ltd., TM Black 3550), an ultraviolet absorber C (hydroxyphenyltriazine-based compound, manufactured by BASF Japan, Tinuvin 477), an ultraviolet absorber D (benzotriazole-based compound, manufactured by BASF Japan, Tinuvin 384-2) and a solvent (ethyl acetate) were mixed to obtain an adhesive composition having a solid content concentration of 30% and containing 0.5 parts by mass of the crosslinking agent, 0.23 parts by mass of the colorant, and 2.00 parts by mass of the ultraviolet absorber in total, based on 100 parts by mass of the acrylic polymer A. Using the adhesive composition obtained as described above, an adhesive sheet with a release sheet was obtained in the same manner as in Example 1.

[0278] [Example 6]

[0279] <Synthesis of Acrylic Polymer B>

[0280] Acrylic polymer B was prepared by solution polymerization in ethyl acetate. 2-methoxyethyl acrylate monomer (2-methoxy ethyl acrylate, MEA), 2-hydroxyethyl acrylate monomer (2HEA), methyl methacrylate (methyl methacrylate, MMA), dimethyl acrylamide (dimethyl acrylamide, DMAA) and butyl acrylate (BA) were prepared in a mass ratio of 70:10:10:5:5, and azobisisobutyronitrile (AIBN) as a free radical polymerization initiator was dissolved in the solution. The solution was heated to 60°C for random copolymerization to obtain acrylic polymer B. The solution viscosity of a 35% by mass solution of the acrylic polymer B at 23°C was 2,000 mPa·s. In addition, the acid value of acrylic polymer B was 0.0 mgKOH / g.

[0281] <Preparation of Adhesive Composition and Adhesive Sheet>

[0282] An adhesive composition having a solid content concentration of 30% by mass and containing 0.05 parts by mass of the crosslinking agent and 0.11 parts by mass of the coloring agent relative to 100 parts by mass of the acrylic polymer B was obtained by mixing an acrylic polymer B, an epoxy crosslinking agent (N,N,N',N'-tetraglycidyl-1,3-phenylenedi(methylamine), manufactured by Mitsubishi Gas Chemical Co., Ltd., TETRAD-X), an MO coloring agent (copper, iron, manganese oxide, i.e., metal oxide, manufactured by Dainichi Seika Industries, Ltd., TM Black 3550), and a solvent (ethyl acetate). The adhesive composition obtained in the above manner was applied to a thickness of 50 μm after drying, and an adhesive sheet with a release sheet was obtained in the same manner as in Example 1 except that the above-obtained adhesive composition was applied to a thickness of 50 μm after drying.

[0283] [Example 7 to Example 9]

[0284] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 6 except that the amount of the colorant blended was changed so that the content of the MO colorant became the amount described in Table 1 below and the thickness of the adhesive sheet after drying became the thickness described in Table 1 below.

[0285] [Comparative Example 1]

[0286] By mixing acrylic polymer A, epoxy crosslinking agent (N,N,N',N'-tetraglycidyl-1,3-phenylenedi(methylamine), manufactured by Mitsubishi Gas Chemical Co., Ltd., TETRAD-X), CB colorant (carbon black, manufactured by Toyo Color Co., Ltd., Multilac A 903 Black) and solvent (ethyl acetate), an adhesive composition containing 1.1 parts by mass of the crosslinking agent and 0.14 parts by mass of the colorant with a solid content concentration of 30% was obtained based on 100 parts by mass of acrylic polymer A. Using the adhesive composition obtained in the above manner, an adhesive sheet with a release sheet was obtained in the same manner as in Example 1.

[0287] [Comparative Example 2]

[0288] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Comparative Example 1 except that the amount of the colorant blended was changed so that the content of the CB colorant was 0.83 parts by mass and the thickness of the adhesive sheet after drying was changed so that it was 50 μm.

[0289] [Comparative Example 3]

[0290] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Comparative Example 1 except that the amount of the colorant blended was changed so that the content of the CB colorant was 0.28 parts by mass and the thickness of the adhesive sheet after drying was changed so that it was 250 μm.

[0291] [Example 10]

[0292] <Synthesis of Acrylic Polymer C>

[0293] Acrylic polymer C was prepared by solution polymerization in ethyl acetate. Butyl acrylate (BA), 2-ethylhexyl methacrylate (2EHMA), ethyl acrylate (EA), 2-hydroxyethylmethacrylate (2HEMA) and acrylic acid (AA) were prepared in a mass ratio of 85:5:4:4:2, and azobisisobutyronitrile (AIBN) as a radical polymerization initiator was dissolved in the solution. The solution was heated to 60°C for random copolymerization to obtain acrylic polymer C. The solution viscosity of a 35% by mass solution of the acrylic polymer C at 23°C was 3,650 mPa.s. In addition, the acid value of the acrylic polymer C was 1.6 mgKOH / g.

[0294] <Preparation of Adhesive Composition>

[0295] An acrylic polymer C, a crosslinking agent (N,N,N′,N′-tetraglycidyl-1,3-phenylenedi(methylamine, manufactured by Mitsubishi Gas Chemical Co., Ltd., TETRAD-X), an MO colorant (manufactured by Mikoku Color Co., Ltd., MHI Black #PD-367M as titanium oxide) and a solvent (ethyl acetate) were mixed to obtain an adhesive composition having a solid content concentration of 30% and containing 0.1 parts by mass of the crosslinking agent and 1 part by mass of the colorant relative to 100 parts by mass of the acrylic polymer C.

[0296] <Preparation of Adhesive Sheet>

[0297] The adhesive composition was applied to a first release sheet (a heavy release film, a polyethylene terephthalate film produced by Mitsubishi Chemical Co., Ltd., and subjected to a release treatment). The coating was performed using a YD-type scraper produced by Yoshimitsu Seiki Co., Ltd., in such a manner that the thickness after drying was 25 μm. Thereafter, the adhesive sheet having an adhesive layer was formed by drying at 100° C. for 3 minutes using a hot air dryer to remove the solvent.

[0298] A second release sheet (light release film, manufactured by Mitsubishi Chemical Co., Ltd.) having a higher single-sided release property than the first release sheet was subjected to a release treatment to obtain an adhesive sheet with a release sheet, i.e., an adhesive sheet of Example 10. In the adhesive sheet of Example 10, the content per unit area of ​​the MO colorant contained in the adhesive layer was 0.25 g / m 2 .

[0299] [Optical properties measurement]

[0300] The light peeling diaphragm as the second peeling sheet was peeled off from the adhesive sheet of each embodiment and comparative example, and a PET film (manufactured by Toyobo Co., Ltd., Cosmoshine A4300#100) was laminated using a manual roller instead of the peeled diaphragm to produce a laminated film. The laminated film was cut into a size of 50 mm wide and 50 mm long, and the first peeling sheet was peeled off. Then, the exposed adhesive surface was attached to a glass slide (manufactured by Matsunami Glass Co., Ltd., S9112) using a manual roller. In the above state, it was kept in an autoclave at 40°C and 5 atmospheres for 30 minutes to be in close contact with the glass plate.

[0301] The obtained laminated body sample was measured for L*, a*, and b* in the L*a*b* colorimetric system in accordance with JIS Z8781-4: 2013. In addition, the C1 value represented by the following formula 1 was obtained. The obtained results are described in Table 1 below.

[0302] Formula 1:

[0303] C1=0.13×L*-b*

[0304] The slide glass used was colorless and transparent, and the obtained L*, a*, and b* were used as L*, a*, and b* of the adhesive sheet.

[0305] For reference, the following equation 1A, which converts equation 1 into a relationship between L* and b* when the C1 value is a lower limit of 9, the following equation 1B, which converts equation 1 into a relationship between L* and b* when the C1 value is an upper limit of 15, and the plots obtained in the various examples and comparative examples are summarized in Figure 2 middle. Figure 2 The horizontal axis is L* and the vertical axis is b*.

[0306] Formula 1A:

[0307] b*=0.13×L*-9

[0308] Formula 1B:

[0309] b*=0.13×L*-15

[0310] according to Figure 2It is found that the C1 value represented by Formula 1 in the adhesive sheet of each example using the metal oxide satisfies 9 to 15.

[0311] [evaluate]

[0312] <Sense of unity with the black frame>

[0313] Laminated body samples were prepared in the same manner as in the optical property measurement, and were placed on a display including a black frame in a black screen display state and a light-off state (power off) and evaluated. The obtained results are described in Table 1 below.

[0314] ○: Compared with when nothing is placed, the border with the black frame around the display is less noticeable, and the sense of unity is improved.

[0315] ×: No change. Or the border with the black frame around the display is prominent and does not feel integrated.

[0316] <Design>

[0317] A laminate sample was prepared in the same manner as in the optical property measurement, and was placed on a display including a black frame showing a black screen and evaluated. The obtained results are described in Table 1 below.

[0318] ○: Appears darker than when nothing is placed.

[0319] ×: No change.

[0320] [Table 1]

[0321]

[0322] According to Table 1, the adhesive sheet of the present invention obtained in each embodiment has excellent integration with the black frame of the transparent member including the black frame. On the other hand, the adhesive sheet obtained in the comparative example has an a* value that is out of the range of (-3.0 or more) and less than 0, a b* value that is out of the range of less than 0, and does not contain a colorant that is "a metal type containing one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium", and has poor integration with the black frame of the transparent member including the black frame.

[0323] [Example 101]

[0324] <Preparation of Adhesive Composition>

[0325] The acrylic polymer A synthesized in Example 1, an isocyanate crosslinking agent (an ethyl acetate solution of toluene diisocyanate adduct of trimethylolpropane, manufactured by Tosoh Co., Ltd., Coronate L-55E), an MO colorant (copper, iron, and manganese-based oxides, i.e., metal oxides, manufactured by Dainichi Seika Industries, Ltd., TM Black 3550) and a solvent (ethyl acetate) were mixed to obtain an adhesive composition having a solid content concentration of 30% and containing 0.5 parts by mass of the crosslinking agent and 0.40 parts by mass of the colorant relative to 100 parts by mass of the acrylic polymer A.

[0326] <Preparation of Adhesive Sheet>

[0327] The adhesive composition was applied to a first release sheet (a heavy release film, a polyethylene terephthalate film produced by Mitsubishi Chemical Co., Ltd., and subjected to a release treatment). The coating was performed using a YD-type scraper produced by Yoshimitsu Seiki Co., Ltd., in such a manner that the thickness after drying was 100 μm. Thereafter, the adhesive sheet having an adhesive layer was formed by drying at 100° C. for 3 minutes using a hot air dryer to remove the solvent.

[0328] A second release sheet (light release film, manufactured by Mitsubishi Chemical Co., Ltd.) having a higher single-sided release property than the first release sheet was subjected to a release treatment to obtain an adhesive sheet with a release sheet, i.e., an adhesive sheet of Example 101. In the adhesive sheet of Example 101, the content per unit area of ​​the MO colorant contained in the adhesive layer was 0.4 g / m 2 In the adhesive sheets of other examples and comparative examples, the content per unit area of ​​the MO colorant contained in the adhesive layer is proportional to the blending amount of the MO colorant in the adhesive composition and the thickness of the adhesive sheet after drying.

[0329] [Example 102 to Example 104]

[0330] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 101 except that the amount of the colorant blended was changed so that the content of the MO colorant would be the amount described in Table 2 below.

[0331] [Example 105]

[0332] By mixing acrylic polymer A, isocyanate crosslinking agent (ethyl acetate solution of toluene diisocyanate adduct of trimethylolpropane, manufactured by Tosoh Co., Ltd., Coronate L-55E), MO colorant (copper, iron, manganese oxide, i.e. metal oxide, manufactured by Dainichi Seika Co., Ltd., TM Black 3550), ultraviolet absorber D (benzotriazole compound, manufactured by BASF Japan Co., Ltd., Tinuvin 384-2) and solvent (ethyl acetate), an adhesive composition containing 0.5 parts by mass of crosslinking agent, 1.00 parts by mass of colorant, 6.00 parts by mass of ultraviolet absorber and having a solid content concentration of 30% with respect to 100 parts by mass of acrylic polymer A was obtained. The adhesive composition obtained in the above manner was used, and the thickness of the adhesive sheet after drying was changed to 50 μm, and an adhesive sheet with a release sheet was obtained in the same manner as in Example 101 except that it was changed.

[0333] [Example 106 to Example 109]

[0334] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Example 105 except that the amount of the colorant blended was changed so that the content of the MO colorant became the amount described in Table 2 below and the thickness of the adhesive sheet after drying became the thickness described in Table 2 below.

[0335] [Comparative Example 101]

[0336] By mixing acrylic polymer A, isocyanate crosslinking agent (ethyl acetate solution of toluene diisocyanate adduct of trimethylolpropane, manufactured by Tosoh Co., Ltd., Coronate L-55E) and solvent (ethyl acetate), an adhesive composition containing 0.5 parts by mass of crosslinking agent and a solid content concentration of 30% by mass relative to 100 parts by mass of acrylic polymer A was obtained. The adhesive composition obtained in the above manner was used, and the thickness of the adhesive sheet after drying was changed to 25 μm. An adhesive sheet with a release sheet was obtained in the same manner as in Example 101.

[0337] [Comparative Example 102]

[0338] By mixing acrylic polymer A, isocyanate crosslinking agent (ethyl acetate solution of toluene diisocyanate adduct of trimethylolpropane, manufactured by Tosoh Co., Ltd., Coronate L-55E), CB colorant (carbon black, manufactured by Toyo Color Co., Ltd., Multilac A 903 Black) and solvent (ethyl acetate), an adhesive composition containing 0.5 parts by mass of crosslinking agent and 2.80 parts by mass of colorant with respect to 100 parts by mass of acrylic polymer A and having a solid content concentration of 30% by mass was obtained. The adhesive composition obtained in the above manner was used, and the thickness of the adhesive sheet after drying was changed to 25 μm. In addition, an adhesive sheet with a release sheet was obtained in the same manner as in Example 101.

[0339] [Comparative Example 103]

[0340] An adhesive composition and an adhesive sheet with a release sheet were obtained in the same manner as in Comparative Example 102 except that the amount of the colorant blended was changed so that the content of the CB colorant became 4.40 parts by mass.

[0341] [Example 110]

[0342] The adhesive composition and the adhesive sheet with a release sheet were obtained in the same manner as in Example 10 except that the amount of the colorant was changed so that the content of the titanium oxide MO colorant used in Example 10 was 3 parts by mass. In the adhesive sheet of Example 110, the content per unit area of ​​the colorant contained in the adhesive layer was 0.75 g / m 2 .

[0343] [Example 111]

[0344] The adhesive composition and the adhesive sheet with a release sheet were obtained in the same manner as in Example 10 except that the amount of the colorant was changed so that the content of the titanium oxide MO colorant used in Example 10 was 2 parts by mass. In the adhesive sheet of Example 111, the content per unit area of ​​the colorant contained in the adhesive layer was 0.50 g / m 2 .

[0345] [Optical properties measurement]

[0346] A laminate sample was obtained by the same method as in Example 101, and L*, a*, and b* in the L*a*b* colorimetric system were measured in accordance with JIS Z8781-4:2013. In addition, the C2 value represented by the following formula 2 was determined. The obtained results are described in Table 2 below.

[0347] Formula 2:

[0348] C2=0.06×L*-b*

[0349] The slide glass used was colorless and transparent, and the obtained L*, a*, and b* were used as L*, a*, and b* of the adhesive sheet.

[0350] For reference, the following formula 2A, which converts formula 2 into a relationship between L* and b* when the C2 value is a lower limit of 5.8, the following formula 2B, which converts formula 2 into a relationship between L* and b* when the C2 value is an upper limit of 10.8, and the plots a* and b* obtained in each embodiment and comparative example are summarized in Figure 3 middle. Figure 3 The horizontal axis is L*, and the vertical axis is a* or b*.

[0351] Formula 2A:

[0352] b*=0.06×L*-5.8

[0353] Formula 2B:

[0354] b*=0.06×L*-10.8

[0355] according to Figure 3 From the drawing of the examples (b*), it can be seen that the C2 value represented by Formula 2 in the adhesive sheets of each example using the metal oxide satisfies 5.8 to 10.8.

[0356] [evaluate]

[0357] <Sense of unity with the black frame>

[0358] The ultraviolet curable ink was screen-printed on the surface of a glass plate (120 mm in length, 70 mm in width, and 0.7 mm in thickness) in a frame shape (inner edge dimensions: 90 mm in length, 50 mm in width, and 5 mm in width) so that the coating thickness was 5 μm. Then, the printed ultraviolet curable ink was cured by irradiation with ultraviolet rays. Through the above steps, a printed step glass plate with a step difference of 5 μm was obtained.

[0359] The light peeling separator as the second peeling sheet was peeled off from the adhesive sheet of each embodiment and comparative example, and a PET film (manufactured by Toyobo Co., Ltd., Cosmoshine A4300#100) was laminated using a manual roller instead of the peeled separator to produce a laminated film. The laminated film was cut into a size of 55 mm wide and 95 mm long, and the first peeling sheet was peeled off. Then, the exposed adhesive surface was attached to the printed step glass plate using a manual roller. In the above state, it was kept in an autoclave at 40°C and 5 atmospheres for 30 minutes to be in close contact with the glass plate.

[0360] The prepared samples were placed on a display in a state where a black screen was displayed and a light-off state (when the power was off) and evaluated. The obtained results are described in Table 2 below.

[0361] ◎: The inner boundary between the black frames is not prominent and looks integrated.

[0362] ○: Compared with when nothing is placed, the border with the black frame around the display is less noticeable, and the sense of unity is improved.

[0363] ×: No change. Or the border with the black frame around the display is prominent and does not feel integrated.

[0364] <Design>

[0365] A laminate sample was prepared in the same manner as in the optical property measurement, and was placed on a display including a black frame showing a black screen and evaluated. The obtained results are described in Table 2 below.

[0366] ◎: Looks darker and emphasizes blackness.

[0367] ○: Appears darker than when nothing is placed.

[0368] ×: No change.

[0369] <Visibility>

[0370] Laminated body samples were prepared in the same manner as in the optical property measurement, and the brightness of the display showing characters was adjusted to 500 nit, and evaluated according to the following criteria. The obtained results are shown in the following Table 2. In addition, the evaluation of visibility as ○ is preferred in practical terms.

[0371] ○: No bleeding or blurring was observed.

[0372] △: Bleeding and blurring were observed, but the text was still recognizable.

[0373] ×: Bleeding and blurring were observed and the text was unrecognizable.

[0374] [Table 2]

[0375]

[0376] According to Table 2, the adhesive sheet of the present invention obtained in each embodiment has excellent integration with the black frame of the transparent component including the black frame. On the other hand, the b* value of the adhesive sheet obtained in Comparative Example 101 is out of the range of less than 0, does not contain a colorant as "the metal type contains one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium", and has poor integration with the black frame of the transparent component including the black frame. In addition, the a* value of the adhesive sheets obtained in Comparative Examples 102 and 103 is out of the range of (above -3.0) and less than 0, the b* value is out of the range of less than 0, does not contain a colorant as "the metal type contains one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium", and has poor integration with the black frame of the transparent component including the black frame.

Claims

1. An adhesive sheet comprising an acrylic polymer and a colorant, wherein: The colorant is a metal oxide, The adhesive sheet is used to adhere to the transparent member including the black frame. The adhesive sheet has an L* value of 15 or more and less than 90, an a* value of less than 0, and a b* value of less than 0 in the L*a*b* colorimetric system specified in Japanese Industrial Standard Z8781-4:2013, wherein the L* value of the adhesive sheet is 60 or more and less than 90, and the C1 value represented by the following formula 1 is 9 to 15, or The L* value is 15 or more and less than 60, and the C2 value represented by the following formula 2 is 5.8 to 10.8, Formula 1: C1=0.13×L*-b* Formula 2: C2 = 0.06 × L* - b*. 2 . The adhesive sheet according to claim 1 , wherein the colorant comprises at least one metal species containing one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium.

3. An adhesive sheet comprising an acrylic polymer and a colorant, wherein: The colorant comprises at least one metal species containing one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium, The adhesive sheet is used to adhere to the transparent member including the black frame. The adhesive sheet has an L* value of 15 or more and less than 90, an a* value of less than 0 in the L*a*b* colorimetric system specified in Japanese Industrial Standard Z8781-4:2013, wherein the L* value of the adhesive sheet is 60 or more and less than 90, and the C1 value represented by the following formula 1 is 9 to 15, or The L* value is 15 or more and less than 60, and the C2 value represented by the following formula 2 is 5.8 to 10.8, Formula 1: C1=0.13×L*-b* Formula 2: C2 = 0.06 × L* - b*. 4 . The adhesive sheet according to claim 1 , wherein the colorant is a black metal oxide.

5. An adhesive sheet comprising an acrylic polymer and a colorant, wherein: The colorant is a black metal oxide. The adhesive sheet is used to adhere to the transparent member including the black frame. The adhesive sheet has an L* value of 15 or more and less than 90, and an a* value of -10.0 or more and less than 0 in the L*a*b* colorimetric system specified in Japanese Industrial Standard Z8781-4:2013, wherein the L* value of the adhesive sheet is 60 or more and less than 90, and the C1 value represented by the following formula 1 is 9 to 15, or The L* value is 15 or more and less than 60, and the C2 value represented by the following formula 2 is 5.8 to 10.8, Formula 1: C1=0.13×L*-b* Formula 2: C2 = 0.06 × L* - b*. 6 . The adhesive sheet according to claim 1 , wherein the a* value of the adhesive sheet is greater than or equal to −3.0 and less than −0.2, and the b* value is greater than or equal to −20.0 and less than 0. 7 . The adhesive sheet according to claim 1 , wherein the acrylic polymer contains acrylic acid monomer units having a crosslinkable functional group. 8 . The adhesive sheet according to claim 1 , further comprising a cross-linking agent. 9 . The adhesive sheet according to claim 1 , further comprising a UV absorber. 10 . The adhesive sheet according to claim 1 , wherein the C1 value is 11 to 13, or the C2 value is 7.8 to 9.

8.

11. A method for producing an adhesive sheet, the adhesive sheet comprising an acrylic polymer and a colorant, wherein: The colorant is a metal oxide, The adhesive sheet is used to adhere to a transparent component including a black frame, and the manufacturing method of the adhesive sheet includes any one of the following steps: The step of screening the adhesive sheet, wherein the L* value in the L*a*b* color system specified in Japanese Industrial Standard Z8781-4:2013 is greater than 15 and less than 90, the a* value is less than 0, and the b* value is less than 0; A step of screening the adhesive sheet, wherein the colorant in the adhesive sheet comprises at least one metal type containing one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium, and the L* value is greater than 15 and less than 90, and the a* value is less than 0; and The step of screening the adhesive sheet, wherein the L* value of the adhesive sheet is greater than 15 and less than 90, and the a* value is greater than -3.0 and less than 0, wherein the L* value of the adhesive sheet is 60 or more and less than 90, and the C1 value represented by the following formula 1 is 9 to 15, or The L* value is 15 or more and less than 60, and the C2 value represented by the following formula 2 is 5.8 to 10.8, Formula 1: C1=0.13×L*-b* Formula 2: C2 = 0.06 × L* - b*.

12. A method for selecting a colorant, wherein the colorant is used for an adhesive sheet comprising an acrylic polymer and a colorant, wherein: The colorant is a metal oxide, The adhesive sheet is used to adhere to the transparent member including the black frame. When the adhesive sheet is manufactured using the acrylic polymer and the colorant, the method includes any one of the following steps: The step of selecting the colorant of the adhesive sheet having an L* value of 15 or more and less than 90, an a* value of less than 0, and a b* value of less than 0 in the L*a*b* color system specified in Japanese Industrial Standard Z8781-4:2013; A step of selecting the colorant including at least one metal species containing one or more metal oxides selected from the group consisting of copper, iron, manganese and titanium, and the L* value of the adhesive sheet is greater than 15 and less than 90, and the a* value is less than 0; and The step of selecting the colorant having the L* value of 15 or more and less than 90 and the a* value of -3.0 or more and less than 0, wherein the L* value of the adhesive sheet is 60 or more and less than 90, and the C1 value represented by the following formula 1 is 9 to 15, or The L* value is 15 or more and less than 60, and the C2 value represented by the following formula 2 is 5.8 to 10.8, Formula 1: C1=0.13×L*-b* Formula 2: C2 = 0.06 × L* - b*.

Citation Information

Patent Citations

  • Double-sided pressure-sensitive adhesive sheet

    JP2005060435A

  • Black foil-like adhesive and black adhesive sheet

    JP2013032430A

  • Optically clear adhesive sheet, method for manufacturing optically clear adhesive sheet, laminate, display device with touch panel, and method for bonding optically clear adhesive sheet

    CN109923188A

  • Adhesive tape or sheet having reflectivity and / or light shielding property

    JP2011127131A

  • Colored photosensitive resin composition, patterning process, method for manufacturing color filter, color filter and display device having the same

    JP2012194516A